The impact of shot size and duration of peening on the enhancement of wrench socket fatigue lifespan - Hsuan-Han Lai; Kun Ming Chiu; Weite Wu (Journal of Materials Research and Technology)
Fatigue cracking is the predominant mode of fracture observed in wrench sockets. Among the various techniques employed to enhance fatigue resistance, shot peening is the most widely utilized method. This study aims to investigate the effects of shot size (0.3 mm, 0.6 mm, and 0.8 mm) and peening duration (5 min and 10 min) on the fatigue lifespan of wrench sockets subjected to shot peening. The application of larger shot sizes resulted in significant grain deformation and refinement on the outer wall, particularly with the 0.8 mm particle size. It was observed that an extended peening duration corresponded to an increased depth of impact, with the outer wall of the socket exhibiting a deeper deformation layer compared to the inner wall. Additionally, the increase in shot size was associated with a notable rise in surface roughness; however, prolonging the treatment duration could mitigate the roughness of the outer wall to a certain extent, while the roughness of the inner wall slightly increased. The surface hardness of the sockets exhibited a significant increase following shot peening, with larger particle sizes contributing to more pronounced enhancements in hardness. Residual stress analysis suggested that the use of smaller shot sizes (0.3 mm) could lead to the introduction of higher compressive residual stresses within both the outer and inner walls of the socket compared to the other two shot sizes. The samples subjected to 0.3 mm shots demonstrated a fatigue lifespan enhancement of 250 % with a 5-min duration and 273 % with a 10-min duration, while those subjected to 0.8 mm shots exhibited enhancements of 79 % with a 5-min duration and 98 % with a 10-min duration. The impact of residual stress on fatigue life was found to be more significant than that of hardness and peening depth.